2016
DOI: 10.1016/j.jare.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

N-succinyl chitosan–dialdehyde starch hybrid hydrogels for biomedical applications

Abstract: A new class of injectable, biocompatible and biodegradable hydrogel is reported. This hydrogel is derived from N-succinyl chitosan (SCS) mixed with water-soluble dialdehyde starch (DAS) without using a conventional chemical crosslinker. The hybrid hydrogel is formed owing to the Schiff’s base reaction between amine groups of SCS and dialdehyde groups of DAS to form —CHN— group. SCS, DAS, and SCS–DAS hybrid hydrogels were synthesized and then characterized by FTIR analysis spectroscopy. The influence of SCS:DAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 28 publications
3
57
0
4
Order By: Relevance
“…To overcome the flaw of water insolubility, N-succinyl chitosan-dialdehyde starch mixture hydrogel was prepared with good solubility to repair cartilage defects (Kamoun, 2016). In addition, the sensitization and mechanism of chitosan may also need improvement in its clinical transformation.…”
Section: Chitosanmentioning
confidence: 99%
“…To overcome the flaw of water insolubility, N-succinyl chitosan-dialdehyde starch mixture hydrogel was prepared with good solubility to repair cartilage defects (Kamoun, 2016). In addition, the sensitization and mechanism of chitosan may also need improvement in its clinical transformation.…”
Section: Chitosanmentioning
confidence: 99%
“…Although the presence of hydroxyl and amino groups in the chitosan molecule can allow structural modification to be easily carried out, in terms of conjugates that result in chitosan conjugates with more structural diversity, it is very necessary to explore a functional group conversion strategy to introduce new reactive groups to the chitosan backbone. It has been demonstrated that the amino group of chitosan can be converted into azide group [87], substituted carboxyl group [88], substituted mercapto group [89], etc., and the hydroxyl group can be azidated [90], aminated [91,92], oxidized to an aldehyde [93] or carbonyl group [94], or further oxidized to a carboxyl group [95]. Figure 4 lists some common functional group conversion methods used in the preparation of common chitosan conjugates.…”
Section: Functional Group Conversion Strategymentioning
confidence: 99%
“…Para la solubilización y modificación química del quitosano se utilizó el protocolo propuesto por Ono. K. y colaboradores [10] ; en el cual se funcionaliza el quitosano por medio de reacciones de carbodiimida con el ácido lactobionico y ácido azidobenzoico para aumen-tar la solubilidad del quitosano a pH fisiológico y producir un hidrogel por fotoentrecruzamiento, respectivamente. Para este proceso se utilizó quitosano con un peso molecular promedio de 4.3x10 5 Da.…”
Section: Elaboración De Los Hidrogeles De Quitosano Modificado: Nano-unclassified
“…La fase de adhesión celular se lleva a cabo en períodos más largos e involucra moléculas de adhesión y del citoesqueleto (como filamentos de actina), los cuales van a interactuar para producir una respuesta bien sea en proliferación o diferenciación celular [24] . química del producto final [10,[25][26] .…”
Section: Evaluación De La Morfología Celular E Interacción Con Biomatunclassified
See 1 more Smart Citation